2016
DOI: 10.1016/j.sse.2015.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Gamma and proton irradiation effects and thermal stability of electrical characteristics of metal-oxide-silicon capacitors with atomic layer deposited Al2O3 dielectric

Abstract: The radiation hardness and thermal stability of the electrical characteristics of atomic layer deposited Al2O3 layers to be used as passivation films for silicon radiation detectors with slim edges are investigated. To directly measure the interface charge and to evaluate its change with the ionizing dose, metal-oxide-silicon (MOS) capacitors implementing differently processed Al2O3 layers were fabricated on p-type silicon substrates. Qualitatively similar results are obtained for degradation of capacitance-vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…On the other hand, the mobile interface charge increases with radiation dose for the O 3 and H 2 O + O 3 oxidants, but the increase is less for the H 2 O + O 3 combination. The observation of no change in oxide charge or saturation of positive charge accumulation resemble earlier irradiation experiments on MOS capacitors with Al 2 O 3 thin films for lower doses up to 300 kGy, where little effect of irradiation on the charge was reported [38,39]. However, in these studies films deposited with H 2 O were concluded as more radiation-hard, and accumulation of mobile charge in form of a hysteresis was not significant.…”
Section: Jinst 16 P05011supporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, the mobile interface charge increases with radiation dose for the O 3 and H 2 O + O 3 oxidants, but the increase is less for the H 2 O + O 3 combination. The observation of no change in oxide charge or saturation of positive charge accumulation resemble earlier irradiation experiments on MOS capacitors with Al 2 O 3 thin films for lower doses up to 300 kGy, where little effect of irradiation on the charge was reported [38,39]. However, in these studies films deposited with H 2 O were concluded as more radiation-hard, and accumulation of mobile charge in form of a hysteresis was not significant.…”
Section: Jinst 16 P05011supporting
confidence: 81%
“…Furthermore, films deposited with O 3 have been shown to trap charges more efficiently than films deposited with water [40]. Our high-resistivity MCz substrates may also be more sensitive to interface traps and mobile charges manifested as hysteresis of MOS capacitor C-V curves, than the substrates with higher doping concentration used in [38].…”
Section: Jinst 16 P05011mentioning
confidence: 88%
“…On the other hand, the mobile interface charge increases with radiation dose for the O 3 and H 2 O + O 3 oxidants, but the increase is less for the H 2 O + O 3 combination. The observation of no change in oxide charge or saturation of positive charge accumulation resemble earlier irradiation experiments on MOS capacitors with Al 2 O 3 thin films for lower doses up to 300 kGy, where little effect of irradiation on the charge was reported [130,131]. However, in these studies films deposited with H 2 O were concluded as more radiation-hard, and accumulation of mobile charge in form of a hysteresis was not significant.…”
supporting
confidence: 81%
“…The oxide layer may gain a more positive charge during the first few Mrad of the ionizing dose, counteracting the negative charge from alumina. However, details of the sample preparation process were found to be important for the radiation resistance of the alumina layer [16], which may explain the performance variability observed at low fluences [14]. We considered both nonirradiated and irradiated samples in this study of surface recombination to find radiationinduced changes.…”
Section: Samples and Measurement Regimesmentioning
confidence: 99%